Analisis Fenomenologi Program Billionairestore “Jago Jualan” Dalam Paradigma Baru Customer Path 5A - Nur Elisa Faizaty (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background - Strategy formulation is often a complicated process that requires adopting a systematic approach to diagnosing external factors and to match these external factors with internal capabilities, therefore strategy formulation is an important measure of a company's success in winning the competition at the national level or maybe even at the international level. Purpose – This study aims to provide an academic paper on freight Forwarder company management which is the object of research in determining future company strategies by identifying SWOT and TOWS in order to uncover strategies to exploit strengths and opportunities as well as to improve weaknesses and overcome these threats. Design/ Methodology/ Approach – This study uses a qualitative approach in answering the formulation of research problems. The data collection method consists of a comprehensive review of the literature and a part of interviews with management executives at freight forwarders. Data analysis uses the IFE approach and the EFE Matrix, to map the scores and weightings of internal strengths and external changes. Result and Discussion – Combining the IFE and EFE analysis, we get a company positioning plot at the medium or hold and maintain level, which means that the company's current focus is on market penetration and product / service development. Conclusion – The TOWS matrix produces a series of proposed strategies, namely SO, WO, ST, and WT that echo internal and external conditions, so it is hoped that the four proposed strategies will be able to increase the competitiveness of companies in the national arena. Research Limitation - This research is limited to companies within the scope of freight forwarders in the city of Surabaya. Research in different years with the same variables is suggested to be carried out in the future, considering that internal changes and external changes will follow changes in time. Research Implications - This research can be used as a reference for other companies in the freight forwarder sector to determine the direction of the company's future strategy, however, these results are only valid for companies that are the object of research, all variables must be changed and adjusted to the conditions of each company. the proposed strategy becomes valid. Acknowledgment - This research was carried out in collaboration with companies in the field of freigt forwarders in the city of Surabaya, along with their leaders who took the time and willingness to complete this research study.